1989
DOI: 10.1139/e89-058
|View full text |Cite
|
Sign up to set email alerts
|

A regional perspective of the Quetico metasedimentary belt, Superior Province, Canada

Abstract: Alternating greenstone-granite and metasedimentary gneiss belts are a first-order tectonic feature of the southem Superior Province. The tectonic development of the Quetico metasedimentary belt is reviewed with regard to depositional, structural, and metamorphic-plutonic history. Over its 1200 km length, the belt consists of marginal metasedimentary schists of turbiditic origin and interior metasedimentary migmatite and peraluminous leucogranite. Polyphase deformation has resulted in a steep easterly-striking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
8

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 45 publications
6
24
0
8
Order By: Relevance
“…Deformation D2 in this area occurred between 2,689+3/-2 Ma and 2,684+6/-3 Ma, similar to the age suggested by Davis and others (1989) for D2 in the Rainy Lake wrench zone. These ages are compatible with the less precise isotopic ages on rocks in northern Minnesota and Michigan (Peterman, 1979), and it seems probable that the rocks and structures throughout the Wawa and Quetico subprovinces are approximately coeval (Percival, 1989). Although convergence along the GLTZ undoubtedly was diachronous, collision probably occurred in the approximate interval 2,692-2,686 Ma (Davis and others, 1989).…”
Section: E10 Precambrian Geology Of Lake Superior Regionsupporting
confidence: 58%
“…Deformation D2 in this area occurred between 2,689+3/-2 Ma and 2,684+6/-3 Ma, similar to the age suggested by Davis and others (1989) for D2 in the Rainy Lake wrench zone. These ages are compatible with the less precise isotopic ages on rocks in northern Minnesota and Michigan (Peterman, 1979), and it seems probable that the rocks and structures throughout the Wawa and Quetico subprovinces are approximately coeval (Percival, 1989). Although convergence along the GLTZ undoubtedly was diachronous, collision probably occurred in the approximate interval 2,692-2,686 Ma (Davis and others, 1989).…”
Section: E10 Precambrian Geology Of Lake Superior Regionsupporting
confidence: 58%
“…Based on the similarity of rock types and sedimentary features, Percival (1989) suggested that the Quetico, Nemiscau, Opinaca and Ashuanipi subprovinces ( Fig. 1 (Percival & Sullivan 1988;Davis et al 1990;Fralick & Davies 1999;Zaleski et al 1999).…”
Section: The Regional Settingmentioning
confidence: 99%
“…Simplified geological map of the Superior province modified from Percival (1989) showing the location of the Ashuanipi subprovince at the eastern end of the Opmaca, Nemiscau and Quetico line of metasedimentary belts.…”
Section: * Plutonicmentioning
confidence: 99%
See 2 more Smart Citations